Identifying in vivo inflammation using magnetic nanoparticle spectra. (11th June 2020) - Weaver, John B; Ness, Dylan B; Fields, Jennifer; Jyoti, Dhrubo; Gordon-Wylie, Scott W; Berwin, Brent L; Mirza, Sohail; Fiering, Steven N
Abstract: We are developing magnetic nanoparticle (NP) methods to characterize inflammation and infection in vivo . Peritoneal infection in C57BL/6 mice was used as a biological model. An intraperitoneal NP injection was followed by measurement of magnetic nanoparticle spectroscopy of Brownian rotation (MSB) spectra taken over time. MSB measures the magnetization of NPs in a low frequency alternating magnetic field. Two groups of three mice were studied; each group had two infected mice and one control with no infection. The raw MSB signal was compared with two derived metrics: the NP relaxation time and number of NPs present in the sensitive volume of the receive coil. A four compartment dynamic model was used to relate those physical properties to the relevant biological processes including phagocytic activity and migration. The relaxation time increased over time for all of the mice as the NPs were absorbed. The NP number decreased over time as the NPs were cleared from the sensitive volume of the receive coil. The composite p-values for all three rate constants were significant: raw signal, 0.0002, relaxation, <10 −16 and local NP clearance, <10 −16 . However, not all the individual mice had significant changes: Only half the infected mice had significantly different rate constants for raw signal reduction. All infected mice had significantly smaller relaxation time constants. All but one of the infected mice had significantly lower rate constants for local clearance. Relaxation is affected by both phagocytic activity, edema and temperature changes and it should be possible to better isolate those effects to more completely characterize inflammation using more advanced MSB methods. The MSB NP signal can be used to identify inflammation in vivo because it has the unique ability to monitor phagocytic absorption through relaxation measurements.